2013
DOI: 10.1007/s00268-013-1988-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Carcinoembryonic Antigen Level Predicts Prognosis in Patients with Pseudomyxoma Peritonei Treated with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy

Abstract: Our results indicated that preoperative CEA levels are useful in predicting the extent of disease and surgical success as well as progress-free and overall survival in patients with PMP treated with cytoreductive surgery and HIPEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
3
21
0
2
Order By: Relevance
“…Serum CEA levels may thus predict the probability of reaching complete cytoreduction in the surgery. Between LG and HG forms of the disease, we could not demonstrate any significant difference in the percentages of elevated CEA levels, similarly to that reported by Canbay et al [17]. In the aggressive HG tumors showing nonpolarized staining pattern, the serum CEA levels were normal, albeit with high tissue content of immunoreactive CEA and PCI values higher than 18.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Serum CEA levels may thus predict the probability of reaching complete cytoreduction in the surgery. Between LG and HG forms of the disease, we could not demonstrate any significant difference in the percentages of elevated CEA levels, similarly to that reported by Canbay et al [17]. In the aggressive HG tumors showing nonpolarized staining pattern, the serum CEA levels were normal, albeit with high tissue content of immunoreactive CEA and PCI values higher than 18.…”
Section: Discussionsupporting
confidence: 90%
“…When we compared the preoperative serum CEA levels and the PCI values, these 2 values showed clear correlation (P b .001). Recently, Canbay et al [17] have also reported association between preoperative CEA levels and PCI in a study comprised of 449 PMP patients. Serum CEA levels may thus predict the probability of reaching complete cytoreduction in the surgery.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, PMP patients with normal levels of these tumor markers have an overall improved prognosis. In the recent study by Canbay et al, researchers concluded that preoperative CEA levels are useful in predicting the extent of disease and surgical success as well as progress-free and overall survival in patients with PMP treated with cytoreductive surgery and hyperthermic intraoperative peritoneal chemotherapy (HIPEC) [16]. These results agree with our case, where a progression of disease was observed postoperatively, given the high CEA and Ca 19-9 serum levels preoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…Levels of carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19‐9 and cancer antigen 125 (CA125) may be raised in these patients. Some studies have shown that increase in one or more of these tumour markers may be associated with worse prognosis.…”
Section: Introductionmentioning
confidence: 99%